MicroRNA‐125b induces tau hyperphosphorylation and cognitive deficits in Alzheimer's disease. (7th July 2014) - Banzhaf‐Strathmann, Julia; Benito, Eva; May, Stephanie; Arzberger, Thomas; Tahirovic, Sabina; Kretzschmar, Hans; Fischer, André; Edbauer, Dieter
Abstract Sporadic Alzheimer's disease (AD) is the most prevalent form of dementia, but no clear disease‐initiating mechanism is known. Aβ deposits and neuronal tangles composed of hyperphosphorylated tau are characteristic for AD. Here, we analyze the contribution of microRNA‐125b (miR‐125b), which is elevated in AD. In primary neurons, overexpression of miR‐125b causes tau hyperphosphorylation and an upregulation of p35, cdk5, and p44/42‐MAPK signaling. In parallel, the phosphatases DUSP6 and PPP1CA and the anti‐apoptotic factor Bcl‐W are downregulated as direct targets of miR‐125b. Knockdown of these phosphatases induces tau hyperphosphorylation, and overexpression of PPP1CA and Bcl‐W prevents miR‐125b‐induced tau phosphorylation, suggesting that they mediate the effects of miR‐125b on tau. Conversely, suppression of miR‐125b in neurons by tough decoys reduces tau phosphorylation and kinase expression/activity. Injecting miR‐125b into the hippocampus of mice impairs associative learning and is accompanied by downregulation of Bcl‐W, DUSP6, and PPP1CA, resulting in increased tau phosphorylation in vivo. Importantly, DUSP6 and PPP1CA are also reduced in AD brains. These data implicate miR‐125b in the pathogenesis of AD by promoting pathological tau phosphorylation.